2009
DOI: 10.1037/a0015819
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational family solidarity: Value differences between immigrant groups and generations.

Abstract: Although immigrants may be more dependent on their immediate family for support, they may also experience a wider generation-gap in values regarding intergenerational solidarity, because of processes of acculturation. Based on large scale survey data (N = 2,028), differences between first and second generation immigrants in values regarding intergenerational solidarity were examined among family members in the Netherlands with an immigration background from Turkey, Morocco, Suriname, and The Dutch Antilles. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 41 publications
1
80
0
3
Order By: Relevance
“…This study further pinpoints that negative impacts of migration on social support, defined in terms of maintaining contact and visits, have been considerably attenuated by the advent of technological changes in communication like mobile phones and skype (Knodel & Saengtienchai, 2007). Another research also indicates that differences in IGFS values are observed between immigrant groups and generations with first generation immigrants placing higher values on family solidarity compared to second generation immigrants (Merz, Özeke-Kocabas, Oort, & Schuengel, 2009). …”
Section: Intergenerational Family Solidarity (Igfs) In the Context Ofmentioning
confidence: 88%
“…This study further pinpoints that negative impacts of migration on social support, defined in terms of maintaining contact and visits, have been considerably attenuated by the advent of technological changes in communication like mobile phones and skype (Knodel & Saengtienchai, 2007). Another research also indicates that differences in IGFS values are observed between immigrant groups and generations with first generation immigrants placing higher values on family solidarity compared to second generation immigrants (Merz, Özeke-Kocabas, Oort, & Schuengel, 2009). …”
Section: Intergenerational Family Solidarity (Igfs) In the Context Ofmentioning
confidence: 88%
“…White participants' preference for ideal selves corresponding to individualisation indicates that they might not only try to escape the negative evaluation of their ingroup due to apartheid but also come to terms with their minority status. The latter conclusion is informed by studies on minorities within immigrant contexts which demonstrated for instance that minorities value family much more than they value the broader community (e.g., Merz, Oort, Oezeke-Kocabas, & Schuengel, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is uncertainty about whether their children will share the traditional views on providing care between the different generations (the elderly are to be taken care by their children or children-in-law in return for the care they themselves received as children) in the destination context, but these doubts are hardly discussed within the family. Although research has shown that younger-generation migrants place a lower value on family solidarity and internalize the cultural values of the host country more strongly than their parents (Merz et al, 2009), most children still feel responsible and are motivated to take care of their parents or in-laws (Dykstra & Fokkema, 2012). The conditions to take on the full responsibility for such care are more difficult in the European context though: compared to the situation in the home country it is less common for children to share a house with parents or in-laws, children are more likely to live further away, and often both sons and daughters work and accordingly have less time to spend with their parents or in-laws.…”
Section: Every Year I Go For 3 To 6 Months To Suriname To Take Care Omentioning
confidence: 99%